The insubordination of signs : political change, cultural transformation, and poetics of the crisis - Richard, Nelly (Post-contemporary interventions., 2004)
Theorizes the cultural reactions--particularly those within the world of the visual arts, literature, and social science--to the oppression of dictatorship.